IDENTIFIKASI SENYAWA BIOAKTIF PADA ISOLAT BAKTERI BUAH BELIMBING WULUH (Averrhoa bilimbi L.) SEBAGAI AGENSIA HAYATI Xanthomonas oryzae pv. oryzae - Aniza Rachmawati; Agung Suprihadi; Endang Kusdiyantini (Jurnal Akademika Biologi, 2017)
Bilimbi (Averrhoa bilimbi L.) is one of original fruit plants from Indonesia. Bilimbi fruits contain flavonoid, saponin, triterpenoid and tanin that have ability as anti-microbial. Bacteria was isolated from bilimbi fruits expected to be able produce bioactive compounds which can kill pathogenic bacteria such as Xanthomonas oryzae pv. oryzae which caused Bacterial Leaf Blight (BLB). Bacterial Leaf Blight in Indonesia caused harvest losses of 18 – 36 %. Infection was caused by X. oryzae caused the leaf symptoms to turn pale yellow, white, withered, and finally die. The purpose of this research are get bacteria isolate from bilimbi fruits (Averrhoa bilimbi L.) and testing bioactive compounds on bacteria isolate from bilimbi fruits which can inhibit Xanthomonas oryzae pv. oryzae (Xoo) growth. This research use methods, that are isolation of bacteria from bilimbi fruits and isolation of Xanthomonas oryzae pv. oryzae, characterization biochemically, inhibition test, and Thin Layer Chromatography. Obtained two bacteria isolate from bilimbi fruits. They are IBW1 dan IBW2, inhibition zona of IBW1 is 0,15 mm and IBW2 0,35 mm. Both of them have potential in antibacteria of X. oryzae bacteria eventhough in weak catagory. Metabolite secondary compound which play a role in antibacteria of X. oryzae is flavonoid compound. Kata kunci: antibacteria, bilimbi, Thin Layer Chromatography, X. oryzae